2015
DOI: 10.1103/physreva.92.031402
|View full text |Cite
|
Sign up to set email alerts
|

Magic wavelengths in the alkaline-earth-metal ions

Abstract: We present magic wavelengths for the nS -nP 1/2,3/2 and nS -mD 3/2,5/2 transitions, with the respective ground and first excited D states principal quantum numbers n and m, in the Mg + , Ca + , Sr + and Ba + alkaline earth ions for linearly polarized lights by plotting dynamic polarizatbilities of the nS, nP 1/2,3/2 and mD 3/2,5/2 states of the ions. These dynamic polarizabilities are evaluated by employing a relativistic all-order perturbative method and their accuracies are ratified by comparing their static… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 20 publications
9
40
1
Order By: Relevance
“…The reason is that the rate of change of 5s and 5p j (or 4d j ) polarizabilities is low near these magic wavelengths, namely, dα/dω is small. The magic wavelength calculated by Kaur et al [65] using the RCC all-order method lies within our uncertainties.…”
Section: F Uncertainties In the Magic Wavelength Positionssupporting
confidence: 81%
See 2 more Smart Citations
“…The reason is that the rate of change of 5s and 5p j (or 4d j ) polarizabilities is low near these magic wavelengths, namely, dα/dω is small. The magic wavelength calculated by Kaur et al [65] using the RCC all-order method lies within our uncertainties.…”
Section: F Uncertainties In the Magic Wavelength Positionssupporting
confidence: 81%
“…The magic wavelengths near 417 nm lie between the transition energies of the 5s → 5p j spin-orbit doublet. The present calculations of magic wavelengths agree excellently with the RCC all-order results of Kaur et al [65].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Precise knowledge of quadrupole transition matrix elements is essential for characterizing relevant spectral lines. Since the existence of magic wavelengths for the 40 Ca + clock transition has been demonstrated both theoretically [11,12] and experimentally [13], all-optical trapped ion clocks are feasible to be realized in the foreseeable future. One important issue for building such kind of trap is to overcome large ac Stark shifts due to use of high optical power; thus it is necessary to take higher-order effects into account by knowing the corresponding high-order transition matrix elements [14].…”
mentioning
confidence: 99%
“…[6], trapping atoms at λ magic s is the foremost process today in a number of applications such as constructing optical lattice clocks. Following this, a number of experimental and theoretical studies have been reported λ magic s in the neutral atoms [7][8][9][10][11][12][13][14], and recently in the singly charged alkaline earth ions [15,16]. In a remarkable work, Katori et.…”
mentioning
confidence: 99%